2000
DOI: 10.1046/j.1442-9993.2000.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for effects of Spartina anglica invasion on benthic macrofauna in Little Swanport estuary, Tasmania

Abstract: Spartina anglica is an exotic perennial grass that can rapidly colonise the intertidal zone of temperate estuaries and lagoons. Consequently, there is considerable concern about its impact on estuarine flora and fauna. This study provides the first investigation of ecological impacts by S. anglica in Australia. The objective was to investigate the impacts of S. anglica on benthic macroinvertebrate communities inhabiting mudflat and native saltmarsh habitats at Little Swanport estuary, Tasmania. The null hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 30 publications
5
79
2
2
Order By: Relevance
“…In some marshes dominated by S. alterniflora (Zipperer 1996;O'Connell 2002), S. anglica (Jackson 1985), S. foliosa (Levin et al 1998), and a hybrid of Spartina alterniflora 路 S. foliosa (hereafter referred to as ''hybrid Spartina'') (Neira et al 2005), macrobenthic communities exhibit lower densities and fewer species relative to adjacent tidal flats. These differ from existing paradigms that predict positive vegetation effects on macrofaunal abundance and diversity (e.g., Netto and Lana 1999;Hedge and Kriwoken 2000;Pennings and Bertness 2001;Brusati and Grosholz 2006).…”
Section: Introductionmentioning
confidence: 65%
“…In some marshes dominated by S. alterniflora (Zipperer 1996;O'Connell 2002), S. anglica (Jackson 1985), S. foliosa (Levin et al 1998), and a hybrid of Spartina alterniflora 路 S. foliosa (hereafter referred to as ''hybrid Spartina'') (Neira et al 2005), macrobenthic communities exhibit lower densities and fewer species relative to adjacent tidal flats. These differ from existing paradigms that predict positive vegetation effects on macrofaunal abundance and diversity (e.g., Netto and Lana 1999;Hedge and Kriwoken 2000;Pennings and Bertness 2001;Brusati and Grosholz 2006).…”
Section: Introductionmentioning
confidence: 65%
“…Apart from a shift in benthic assemblages, birds may also not able to physically reach benthos living in the marsh vegetation. Researchers studying invasive Spartina have reported altered faunal composition and abundance (e.g., Hedge and Kriwoken 2000;Neira et al 2005) and trophic function .…”
Section: Introductionmentioning
confidence: 99%
“…invasions in diVerent parts of the world. Expanding S. anglica marshes appeared hospitable for native macroinvertebrates in Little Swanport estuary, Australia (Hedge and Kriwoken 2000) and Paranagua Bay, Brazil (Netto and Lana 1999). On the other hand, negative eVects similar to those observed in the present study have been reported at various locations, such as San Francisco Bay (Neira et al 2005), southwest Netherlands (Gribsholt and Kristensen 2003) and south coast of Britain (Frid and James 1989).…”
mentioning
confidence: 99%